Extinct and endangered archaeophytes and the dynamics of their diversity in Poland - Zając, Maria; Zając, Adam; Tokarska-Guzik, Barbara (Biodiversity: Research and Conservation, 2010)
A full list of extinct and endangered archaeophyte species for Poland is presented according to IUCN categories. The species are analysed in respect of their origin and syntaxonomic classification. Endangered archaeophytes should be cultivated in botanical gardens and open-air museums, and next reintroduced to natural sites.